Termorregulação e produção de ovos de galinhas Label Rouge em ambiente equatorial semiárido - Souza Jr, João Batista Freire de (Universidade Federal Rural do Semi-Árido, 2014)
This study aimed to evaluate the effect of corn particle size on performance, egg quality and sensible heat loss, beyond of the regional differences in surface temperature of naked neck laying hens by infrared thermography. In Mossoró-RN, 60 label Rouge chickens in laying stage were distributed in a completely randomized design, where were fed with diets containing different corn particle size or geometric mean diameter (GMD) of 605 µm, 1030 µm and 2280 µm. Environmental variables were measured in center of the shed: black globe temperature (TG) and air (TA), wind speed (U) and relative humidity (RH). Rectal temperature (RT), respiratory rate (RR) and surface temperature (TS) were measured in each bird once a week. For sensible heat loss, RT, RR and TS, the analysis of variance was performed by least squares method and comparison of means by Tukey's test (p<0.05). The results showed that the GMD 2280 µm increased the feed intake, causing elevation in body temperature and respiratory rate in response to increased metabolic heat production. The hens fed with this same GMD showed lower quality eggshell. The sensible heat transfer was, during the study, a heat dissipation mechanism, where the increase in radiation and TA levels caused significant decrease in heat loss by radiation, but heat loss by convection was high in high TA due to increased wind speed. There are regional differences in the TS, where the legs act as thermal windows
Thermorregulation and egg production of Label Rouge hens in an equatorial semi-arid environment
Keywords: Egg Production Label Rouge; Sensible heat loss; Infrared thermography; Laying hens of naked neck; Produção de ovos Label Rouge; Perda de calor sensível; Termografia infravermelha; Galinhas poedeiras de pescoço pelado; CIENCIAS AGRARIAS::MEDICINA VETERINARIA